Roughness Calibration to Improve Flow Predictions in Coarse‐Bed Streams. Issue 6 (14th June 2021) - Ferguson, Robert I.
Abstract: Logarithmic and variable‐power equations that use the bed D 84 grain size as a roughness metric reproduce the general trend of flow resistance in streams with coarse beds, but they are unreliable for predictions in individual reaches. For site‐specific application of these equations, I propose that an effective roughness height can be calibrated by making a single flow measurement. I test this idea using published velocity‐depth data for eight coarse‐bed reaches of varied character. In 52 trials (8 reaches × 2 equations × 3 or 4 alternative calibration measurements), single‐measurement calibration reduced the root‐mean‐square error in predicting velocity at all depths by up to 79% (median 66%) compared to using D 84 . This approach may be useful when prescribing environmental flows, estimating bankfull discharge, or predicting bedload transport in coarse‐bed channels in which Manning's n is likely to vary considerably with discharge. Key Points: Predicting flow resistance using a bed grain size percentile is unreliable in shallow flows over coarse stream beds The alternative of calibrating roughness height in a logarithmic or variable‐power resistance equation is tested using data from eight gravel/cobble/boulder reaches Roughness calibration at a single intermediate flow depth greatly improves predictions of velocity at higher and lower depths